Notch signalling synchronizes the zebrafish segmentation clock but is not needed to create somite boundaries. - Ertuğrul M Ozbudak; Julian Lewis (PLoS Genetics, 2008)
Somite segmentation depends on a gene expression oscillator or clock in the posterior presomitic mesoderm (PSM) and on read-out machinery in the anterior PSM to convert the pattern of clock phases into a somite pattern. Notch pathway mutations disrupt somitogenesis, and previous studies have suggested that Notch signalling is required both for the oscillations and for the read-out mechanism. By blocking or overactivating the Notch pathway abruptly at different times, we show that Notch signalling has no essential function in the anterior PSM and is required only in the posterior PSM, where it keeps the oscillations of neighbouring cells synchronized. Using a GFP reporter for the oscillator gene her1, we measure the influence of Notch signalling on her1 expression and show by mathematical modelling that this is sufficient for synchronization. Our model, in which intracellular oscillations are generated by delayed autoinhibition of her1 and her7 and synchronized by Notch signalling, explains the observations fully, showing that there are no grounds to invoke any additional role for the Notch pathway in the patterning of somite boundaries in zebrafish.